2009
DOI: 10.1158/1055-9965.epi-09-0323
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Telomere Maintenance Genes and Risk of Lung Cancer

Abstract: This study was conducted to comprehensively evaluate the associations between polymorphisms in telomere maintenance genes (TERT, TRF1, TNKS1, TRF2, RAP1, and POT1) and lung cancer risk. We captured 35 polymorphisms in the genes and determined their frequencies in 27 healthy Koreans. Ten haplotype-tagging polymorphisms were examined in a case-control study that consisted of 720 lung cancer patients and 720 healthy controls. The TERTrs2735940 g.C > Tand rs2736098 g.G > A, and TNKS1 rs6985140 g.A > G were signifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 37 publications
4
48
1
Order By: Relevance
“…Varadi, V et al independently found similarity results in breast cancer (Shen et al, 2010). Jin Eun Choi et al found that 8 SNPs of hpot1 in which 2 SNPs are the risk factors in lung cancer (Choi et al, 2009). Hosgood, H. D also found hpot1 genetic variations in lung cancer tissues (Hosgood et al, 2009).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Varadi, V et al independently found similarity results in breast cancer (Shen et al, 2010). Jin Eun Choi et al found that 8 SNPs of hpot1 in which 2 SNPs are the risk factors in lung cancer (Choi et al, 2009). Hosgood, H. D also found hpot1 genetic variations in lung cancer tissues (Hosgood et al, 2009).…”
Section: Discussionmentioning
confidence: 94%
“…Savage, S. A. found some single nucleotide polymorphisms(SNP) of hpot1 in breast cancer (Savage et al, 2007). Others founded 2 SNPs of hpot1 are the risk factors of the lung cancer (Choi et al, 2009). There are hpot1 genetic point variations in the skin cancer (Nan et al, 2011).…”
Section: Expression Of Hpot1 In Hela Cells and The Probability Of Genmentioning
confidence: 99%
“…To date, there have been a few studies on TERT rs2736098 polymorphism and susceptibility to lung cancer. Choi et al (2009) investigated the association of rs2736098 in TERT gene with lung cancer in a Korean population. In their study, the rs2736098 TT genotype was positively related to increased risk of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some genome-wide association studies have reported that the variations in the TERT-CLPTM1L (5p15.33) locus contribute to susceptibility to cancers, and found that TERT rs2736098 and CLPTM1L rs401681 were both associated with risk of lung cancer (Wang et al, 2008;Choi et al, 2009;Chen et al, 2012;Myneni et al, 2013). Our previous study which focused on the association between the two genes and lung cancer, found that TERT and CLPTM1L affected the susceptibility to lung cancer in Chinese women non-smokers (Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, study findings are controversial. According to HapMap data, these discrepancies could reflect different allele frequencies in different ethnicities, or might be affected by cancer types, hereditary factors, and environmental factors (Choi et al, 2009). No report has previously determined whether the CLPTM1L rs401681 polymorphism influences HCC susceptibility, but we found that the CLPTM1L rs401681 CT genotype increased the HCC risk in a Chinese male population.…”
Section: Discussionmentioning
confidence: 63%